Elaboración Y Caracterización De Bloques Cerámicos Extruídos Usando Cenizas De La Combustión De Carbón A Escala De Laboratorio (2020)
Ashes resulting from the combustion of coal used to feed the hive furnaces of the ceramic industry of Norte de Santander, contain potentially hazardous pollutants for the environment and have no practical application so far, for that reason they become a waste material. In this study, a formulation was developed to make a ceramic material composed of a mixture of clay from Norte de Santander (Colombia) and ash residues from the combustion of coal used to feed hive kilns in the region, which were added in proportions of 10, 20 and 30% w/w, forming prototype mixtures of extruded and sintered ceramic blocks in a temperature range between 900 to 1100 ° C, with gradients of 50 ° C. FTIR-ATR was used to identify the presence of different functional groups and the mineralogical composition was studied by DRX of the raw materials; Likewise, the technological behavior of the developed mixtures was evaluated. The results allowed to select the mixture in which 10% of coal ashes and a cooking temperature of 950 ° C were added, since it has a percentage of water absorption and a compressive strength according to the ranges established by the Colombian standards, generating as an added value the lightening and reduction of the cooking temperature, becoming an alternative of innovation and development that can be used in the production processes of traditional materials of the region with an ecological seal.